Partnering Early to Provide for Infants At Risk of Cerebral Palsy (PĒPI ARC): protocol for a feasibility study of a regional hub for early detection of cerebral palsy in Aotearoa New Zealand - Allermo Fletcher, Angelica; Kilgour, Gaela; Sandle, Meghan; Kidd, Sally; Sheppard, Alison; Swallow, Stephanie; Stott, Ngaire Susan; Battin, Malcolm; Korent, Wyllis; Williams, Sian A. (Frontiers in Pediatrics, 2024)
Cerebral palsy (CP) can now be diagnosed as early as three months of age in infants with identified CP risk factors, but many barriers prevent equitable access to early detection pathways. The "Partnering Early to Provide for Infants At Risk of Cerebral Palsy" feasibility study (PĒPI ARC) seeks to trial a new approach to decrease inequitable health service in Aotearoa New Zealand for high-risk infants and their families. PĒPI ARC will incorporate face-to-face clinics, an in-person and virtual Hub, and the use of telehealth to enable flexible access to CP assessments, and support for health professionals in early CP detection.A non-randomised feasibility study will be conducted from the tertiary Neonatal Intensive Care Unit in Wellington and includes seven regional referral centres, servicing nearly 30% of the NZ total population. Families of infants with high risk of neurodevelopmental impairment will be invited to participate, as well as health professionals interacting with the Hub. Mixed methods will be used to evaluate the i) equitable implementation of an early detection pathway, ii) acceptability, iii) demand among families and health professionals, iv) efficacy in relation to reducing the age of receipt of CP diagnosis, and v) the experiences around communication and information sharing.